FNDC5/Irisin counteracts lipotoxic-induced apoptosis in hypoxic H9c2 cells. (August 2019) - Moscoso, Isabel; Cebro-Márquez, María; Rodríguez-Mañero, Moisés; González-Juanatey, José Ramón; Lage, Ricardo
Abstract : Irisin is a newly identified adipokine critical to modulate body metabolism, fatty acid metabolism and oxidative stress; recent evidence suggests a cardioprotective role in ischemic injury. Loss of cardiomyocytes during acute myocardial infarction is strongly associated with energetic changes and lipotoxic-induced apoptosis. Our aim was to study FNDC5/irisin's potential protective role against hypoxia and lipotoxicity, both related with myocardial infarction environment. H9c2 cells were treated with palmitate and/or irisin in normoxic/hypoxic conditions. Cell viability and apoptosis were assessed by MTT assay and annexin V/PI staining. Immunoblotting was used to confirm apoptotic cascade regulation. Irisin counteracts lipotoxic-induced apoptosis in hypoxic cardiomyoblasts by activating Akt signaling pathway suggesting the potential therapeutic role of irisin in ischemic heart disease.